PENGARUH MOTIVASI DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN DI PT ADE MEDIATAMA KOTA TANGERANG - Nazwatul Ummah; Fathorrahman (Journal of Research and Publication Innovation, 2025)
This research aims to determine the influence of motivation variables and the physical work environment on employee performance. This research is included in the type of quantitative research. The sample used was 50 respondents. This research technique uses a saturated sampling technique. Calculations for this research data analysis use the SPSS version 25 application. The analysis used is validity and reliability testing, classical assumption testing, hypothesis testing and multiple linear regression. The results of this research are that motivation and the physical work environment have a significant effect on employee performance at PT Ade Mediatama, Tangerang City.